2014
DOI: 10.1136/bmjopen-2014-005234
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in the early stages of clinical trial development: a systematic cohort investigation

Abstract: BackgroundRandomised controlled trials (RCTs) are considered particularly likely to benefit from patient and public involvement (PPI). Decisions made by professional researchers at the outset may go on to have a significant impact on the potential for PPI contributions.ObjectiveTo increase knowledge of PPI within the early development of RCTs by systematically describing the reported level, nature and acceptability of proposed PPI to the funders.MethodsDocumentation from the outline application process for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 17 publications
1
64
0
Order By: Relevance
“…The trial and participant characteristics restricted to these 90 trials are summarised elsewhere. 69 Of these 90 outline applications, 49 (54%) provided some level of detail on PPI. Table 5 summarises the stage of initiating PPI and role of PPI across the trials.…”
Section: Cohort Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…The trial and participant characteristics restricted to these 90 trials are summarised elsewhere. 69 Of these 90 outline applications, 49 (54%) provided some level of detail on PPI. Table 5 summarises the stage of initiating PPI and role of PPI across the trials.…”
Section: Cohort Summarymentioning
confidence: 99%
“…73,74 However, the funding available is often small and inaccessible to those working within the tight timescales of a typical funding call. 69 Increasing the availability and scale of resource to provide an infrastructure to support researchers and contributors to initiate PPI at the pre-funding stage would help to facilitate earlier implementation.…”
Section: Patient and Public Involvement In Grant Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The most commonly cited challenges, a recent review of the literature indicated, were to do with logistics (extra time and funding needed for patient and public involvement) and, the main worry, a tokenistic approach. 6 Two examples of patient and public involvement initiatives, the Nano-dialogue and Wellbeing dialogue projects, supported by Sciencewise.co.uk, had a total cost of more than half a million pounds in 2007.…”
Section: Encouraging Public Involvementmentioning
confidence: 99%
“…[40][41][42] Reasons for better outcomes include the type of language used in patient-facing information, insights into appropriate or least burdensome study designs, and awareness of patient involvement improving the willingness to be involved. 43 PPI should be carefully planned before research design, incorporating an iterative process where appropriate with clear guidance about roles.…”
Section: Patient and Public Involvementmentioning
confidence: 99%